Low-density aspen seedling establishment is widespread following recent wildfires in the western United States - Kreider, Mark R.; Yocom, Larissa L. (Ecology (Durham), 2021)
Sexual regeneration is increasingly recognized as an important regeneration pathway for aspen in the western United States, a region previously thought to be too dry for seedling establishment except for during unusually wet periods. Because of this historical assumption, information on aspen seedling establishment and factors influencing its occurrence is limited and frequently anecdotal. We conducted a systematic field survey of 15 recent fire footprints that burned in 2018 in the western United States to quantify how common aspen seedling establishment is following fire and to identify factors associated with establishment. We found aspen seedling establishment in 12 of 15 (80%) of fire footprints surveyed, although densities were mostly low. Establishment probability was positively associated with mean annual precipitation and negatively associated with seedsource distance and the density of asexual aspen regeneration. Our results suggest that aspen seedling establishment may be a widespread, if often low-density, feature in postdisturbance areas. Even in low numbers, aspen seedlings may play a disproportionately large role in aspen regeneration ecology, providing adaptive capacity and facilitating local range expansion.